The Effect of DMPA Contraception on Decreased Libido in Couples of Childbearing Age at Bongo II Health Center - Ni Wayan Ariyantini; Widia Shofa Ilmiah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The use of injectable contraceptives with Depo Medroxyprogesterone Acetate (DMPA) is growing in popularity, and is now a common hormonal contraceptive technique. In recipients at the Bango II Health Center, this study aimed to identify changes in sexual function, especially libido, before and after the use of DMPA injectable contraception. The analytical survey technique used in this study uses a cross-sectional approach. The study group included all patients who used DMPA injectable contraceptives at the Bango II Health Center and were registered there. Using basic random sampling, 35 individuals were selected for the sample. The Wilcoxon Signed Rank test is used to assess libido variations before and after the use of DMPA injectable contraception. According to the findings, 14 of the 35 participants experienced a decrease in libido after using DMPA's injectable contraception, while none reported an improvement. Before and after using DMPA, 21 participants reported no change in their libido. After using DMPA injectable contraception, libido changes tended to decrease, as indicated by an average rating value of 7.50 and a rating amount of 105.00 in the decreased libido group. Based on these findings, it can be concluded that the use of DMPA injectable contraceptives at the Bango II Health Center is more likely to be associated with a decrease or no changes in libido in the user, so it is necessary to pay attention in providing contraceptive counseling, especially regarding potential side effects on sexual function.